Caracterização da carne de cabrito do Alto Camaquã: crescimento e desenvolvimento. - Oliveira, Róberson Macedo de (2010)
Twenty three (23) castrated male goats, born in June-July/2008, slaughtered at 11-12 months of age, originating from the familiar raising unit Arroio da Palma, RS, Brazil. Animals were evaluated from Aug/2008 to Jun/2009. During this period production costs were computed and in vivo characteristics taken: body weight, thoraxic perimeter and compacity at 28-days intervals and average weight gain calculated. Prior to slaughter the following parameters were evaluated: anterior and posterior, conformation and body condition. After slaughtering the following parameters were taken: corporal components weight (head, fresh viscera, liver, etc.) and carcass. Also in vivo characteristics and corporal components were evaluated prior to slaughtering in 15 castrated males, born March-April/2009 and sacrificed with 8-9 months of age, originating from the familiar raising unit Casa de Pedra, RS, Brazil. Both units raise animals under extensive range conditions in the region of Alto Camaquã Territory. Data were submitted to analysis of variance (GLM Procedure). Regression analysis was used to obtain alometry coefficients (t-Test P<0.05). Results showed that farm units adopt extensive raising system, animals with undefined breeds, grown in native grasslands and arboreus/brushy vegetation. Goats slaughtered at the age of 11-12 months showed production costs of R$ 0.82/kg liveweight and slaughtering weight was reached in Jan/2009. No significant difference (P>0.05) was found among treatments for the main in vivo characteristics prior to slaughter. Similarity was obtained among treatments for corporal components, the majority of which showed isogonic manner. It is concluded that goats sacrificed at 8-9 months and 11-12 months of age, raised under extensive grazing conditions, in the region of Alto Camaquã, present similarities in the raising process, for in vivo characteristics, prior to slaughtering, and also in corporal components. The optimum age for slaughter, determined in this study, is 8-10 months, weighing 20-22 kg liveweight, as far as the evaluated characteristics are concerned.